PRINSIP KERJASAMA DALAM NOVEL AZAB DAN SENGSARA KARYA MERARI SIREGAR - Annitsa '; Hermandra '; Dudung Burhanudin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstrak: this research discussed the act principle of cooperation in the novelazab dan sengsara by merari siregar. the method used was descriptive method withqualitative approach.in this research, the researcher was used three techniques thatwere read technigue, and record technique. The entire data sourch in the novel Azabdan Sengsara by Merari Siregar. the data of this research amounth to 81 data, fromresult of research which writer find in Novel Azab dan Sengsara by Merari Siregar. theresearch found there were 4 maxsims in the prinsiple of cooperation. Namaly themaxsim of quantity, maxim of quality, maxim of relevance, and maxim of manner.Key words : Principle of Cooperation , Maxsim, and Novel.